Validation of the Thai version of a screening questionnaire for detection of systemic lupus erythematosus - Kasitanon N. (2014)
The present study was performed to assess the sensitivity and specificity of the translation questionnaire for Systemic Lupus Erythematosus (SLE) in Thai speaking populations.